Ocotea glomerata (Nees) mez extract and fractions: Chemical characterization, anti-Candida activity and related mechanism of action - Anjos, MNV (2020)
Background: Opportunistic fungal infections are increasingly common, with Candida albicans being the most common etiological agent; however, in recent years, episodes of candidiasis caused by non-albicans Candida species have emerged. Plants belonging to the Lauraceae family have shown remarkable antifungal effects. This study assessed the anti-Candida activity of Ocotea glomerata extracts and fractions, time of death and the synergistic effects with conventional antifungals. The possible mechanism of action was also addressed. Methods: Minimal inhibitory concentrations (MIC) were determined by broth microdilution technique, and the mechanism of action was assessed by ergosterol, sorbitol, cell viability, reactive oxygen species (ROS) generation and phosphatidylserine externalization tests. Results: All the tested extracts evidenced antifungal activity, but the methanol extract was revealed to be the most effective (MIC = 3.12 µg/mL) on C. krusei. The combination of methanol extract with ketoconazole and fluconazole revealed a synergistic effect for C. krusei and C. albicans, respectively. Fractions 1 and 5 obtained from the methanol extract had fungicidal activity, mainly against C. krusei. Methanol extract did not reveal effects by ergosterol and sorbitol assays; however, it led to an increase in intracellular ROS levels, decreased cell viability, and consequently, cell death. Conclusion: O. glomerata methanol extract may be viewed as a rich source of biomolecules with antifungal activity against Candida spp.